Is Helicobacter pylori a Potential Risk Factor for Lung Cancer? - Fu, Chengfeng (Asian Pacific Journal of Cancer Nursing, 2025)
Helicobacter pylori (H. pylori) is a Gram-negative bacterium known primarily for its role in gastric diseases, including gastric cancer. However, emerging evidence links H. pylori infection to extragastric malignancies, particularly lung cancer. This review examines H. pylori’s biological characteristics, pathogenic mechanisms, and potential association with lung cancer development. It addresses H. pylori’s direct infection pathways, such as aspiration and microbiome transfer, and explores its impact on the immune system via inflammatory responses and molecular mimicry. Epidemiological data demonstrate inconsistent associations between H. pylori infection and lung cancer risk, though some studies suggest H. pylori-derived proteins, like CagA and VacA, might enhance carcinogenicity in lung tissues. Mechanistically, H. pylori-induced upregulation of inflammatory cytokines and cyclooxygenase-2 (COX-2) may contribute to lung carcinogenesis. Understanding these links could inform future therapeutic and preventive strategies for lung cancer in H. pylori-infected individuals. Further research is essential to clarify these associations and underlying mechanisms.